Impact of the anchor borrowers programme on maize productivity in Cross River State, Nigeria - Inah, Michael I.; Egbedi, Ogheneruemu O. (Journal Of Agriculture, Forestry & Environment, 2025)
Maize production in Nigeria is characterized by low productivity caused by wide variety of factors which include low investment as well as problems of financing. Despite various government policies and programmes to addresspoor finance, including the Anchor Borrowers Programmes (ABP), productivity has remained appallingly low, while studies on the programme’s impact on productivity of maize farmers are not abundant. Hence, the impact of Anchor Borrowers Programme on maize productivity in Cross River state, Nigeria was examined. The study used a primary data collected through a semi-structured questionnaire from 250 maize farmers through a multi stagesampling procedure. The result showed that Maize farmers’ age was 41 years and household size was 4 persons. Most farmers were male (78.0%), married (71.2%), had formal education (85.6%), non-members of cooperative(74.8%) and had primary occupation of farming (92.4%). About 73.6% of the farmers were participants of the ABP. Maize farming in Cross River State was productive with a mean productivity of 1.10. Furthermore, the averagetreatment effect showed that the participation of maize farmers in the ABP increased the productivity of maize farmers in Cross River state, Nigeria. Conclusively, Anchor Borrowers Programme increases the productivity ofmaize farmers in Cross River state. Hence, increased participation of maize farmers in the programme should be encouraged.